2001
DOI: 10.1093/annonc/12.suppl_2.s69
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of blood chromogranin A measurement in neuroendocrine tumours

Abstract: CgA was confirmed to be the best tumour marker currently available for identifying patients suffering from NETs of the GEP system, lung carcinoids and neuroblastomas. CgA evaluation is recommended in the follow-up of patients with such tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 10 publications
6
75
1
6
Order By: Relevance
“…Pancreatic polypeptide is a 36 amino acid protein secreted by endocrine cells located primarily in the pancreatic head and uncinate process, with a low sensitivity of 31% in PNETs (25). Neuron-specific enolase is a biomarker with a sensitivity of 33% and a specificity of 100% in patients with gastroenteropancreatic neuroendocrine tumors (26). It is also an independent predictor of survival for patients with advanced G1/2 PNETs undergoing peptide receptor radionuclide therapy (27).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…Pancreatic polypeptide is a 36 amino acid protein secreted by endocrine cells located primarily in the pancreatic head and uncinate process, with a low sensitivity of 31% in PNETs (25). Neuron-specific enolase is a biomarker with a sensitivity of 33% and a specificity of 100% in patients with gastroenteropancreatic neuroendocrine tumors (26). It is also an independent predictor of survival for patients with advanced G1/2 PNETs undergoing peptide receptor radionuclide therapy (27).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…Megfi gyelték, hogy a kissejtes tüdőrák szakaszai és a tumor teljes mérete korrelál a termelődő CgA-koncentrá-cióval [41]. A neuroblastomákban és a pajzsmirigy medullaris carcinomájában szintén emelkedett CgA-szintek fi gyelhetőek meg [42].…”
Section: öSszefoglaló Közleményunclassified
“…Seregni et al [28] and Sivanello et al [29] also demonstrated that the CgA plasma concentration is elevated in patients with tumors NET and strongly correlates with the severity of the neoplastic process.…”
Section: Discussionmentioning
confidence: 94%
“…However in well differentiated tumors low median value of CgA was observed. According to the Seregni et al [28] and Stivanello et al [29] the CgA plasma concentration in NET patients reflects the differentiation grade of neuroendocrine tumor. Furthermore, Giovanella et al [7] results indicate that a very high CgA concentration is a good prognostic marker and may indicate well-differentiated neuroendocrine carcinomas.…”
Section: Discussionmentioning
confidence: 97%